The Correspondence of Dr. Martin Lister (1639-1712). Volume Two: 1678-1694 - Roos, Anna Marie (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
Martin Lister (1639-1712), who served as physician to Queen Anne, was a prominent Fellow of the Royal Society (F.R.S.), and he was made an honorary M.D. by Oxford in 1684.The first scientific arachnologist and conchologist, and a major benefactor of the Ashmolean Museum, he corresponded regularly on natural history and medicine with its first and second keepers, Robert Plot (1640-1696) and Edward Lhwyd (1660-1709). Lister's unpublished papers were among the largest of his donations to Oxford's fledgling museum of science. In the mid-nineteenth century, these collections passed from the Ashmolean to the Bodleian Library. They contain the bulk of his correspondence, though sizeable quantities of his outgoing letters are held elsewhere, chiefly in the Royal Society, the Natural History Museum and the British Library's collection of Sloane Manuscripts. This volume is a critical edition of this correspondence from 1678 to 1694, encompassing the years he established a medical practice in London and completed his major works on conchology.